Investigating the Perspective of Science and Technology Students on the Ulumul Qur’an Course (The Study of Phenomenology in the Learning Process) - Isnaini, Rohmatun Lukluk (Proceeding International Conference on Religion, Science and Education, 2022)
UIN Sunan Kalijaga Yogyakarta has characterizing courses (such as Ulumul Qur’an) that must be taken by all students, including Science and Technology students. There are many assumptions that science and technology students will not be interested in taking this course. Thus, this study aims to investigate the perspective of science and technology students on the Ulumul Qur’an course and to get an overview of the learning process. Through phenomenological qualitative research methods, researchers collected data by interviewing students, participatory observations in the learning process, and study documentation of Semester Learning Plans (RPS). Then, the data acquisition was analyzed through five stages, namely writing down all interview transcripts, finding statements about the focus of the research, grouping these statements into meaningful units, and constructing all explanations about the meaning and essence of the informants’ experiences. The results showed that by using the active learning model, students could express their critical thoughts about religion and the Qur’an. The specified discussion topics can develop broadly to confront general science and religious knowledge and also ask many questions related to belief/aqidah. The findings of this study suggest that the process of learning religious subjects in the Science and Technology class can create awareness about religious and general sciences that cannot be contradicted.